Korelasi Tingkat Absensi Dengan Hasil Belajar Peserta Didik di SMA 4 Negeri Banda Aceh Kelas X IA 1 - Annisa, Fera; Sidqie, Rafif; Maslinda, Maslinda (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
The teacher not only evaluates student learning achievement based on the grades obtained through tests or examinations, but also evaluates one of the levels of attendance. Students who diligently enter will get a positive score in the assessment, and vice versa, if they rarely attend it will have a negative impact on learning outcomes. This study aims to determine and prove the relationship between attendance and student learning outcomes of SMA Negeri 4 Banda Aceh. This study used a quantitative method of 36 students. The sampling technique uses a census sample, which takes all members of the population as a sample. Data collection was carried out by collecting files in the form of learning scores and class absence scores. Data analysis using linear regression analysis. The results of the study show that there is a strong and opposing relationship between absenteeism and student learning outcomes. The conclusion obtained is that the more often students are absent (attendance), the lower their learning outcomes, and vice versa, the more often students attend school, the higher their learning outcomes.